VEP visual acuity in children with cortical visual impairment - Mackay, Alison M (International Journal of Clinical and Experimental Ophthalmology, 2022)
Given improvements in neonatal care and the increased survival rates of infants born pre-term, Cortical Visual Impairment (CVI) is now the leading cause of visual impairment (VI) in the developed world. In this study, Step VEPS, transient VEPS and Vernier Sweep VEPs all demonstrated unbiased relationships with Preferential looking (PL) cards over the whole range of Visual Acuity (VA) in children with CVI, allowing equations for clinical use to be derived. The results also suggested that a slower, vernier steady-state stimulus of 80% contrast and presented with the Step VEP algorithm could further improve VA agreement with PL and optimise developmental sensitivity. An eye tracking device has proved very useful in the clinical assessment of this cohort. It is also now known that children can have good VA and CVI, and that sweep VEPS can highlight higher processing deficits. As well as negative findings, compensatory neuroplasticity is thought to occur during maturation and it is now realistic to study this mechanism, and other age-related changes across VI with functional tests and neuroimaging (including VEPS). A cross-sectional study of adults would highlight CVI’s ultimate functional limitations.